IMPLEMENTASI ETIKA PELAYANAN PUBLIK DI PUSKESMAS LUBUK ALUNG KABUPATEN PARIAMAN - Primananda, Suci (journal of residu, 2019)
The aims of this study are; 1). Identifying the implementation of public service ethics at Lubuk Alung Health Center, Padang Pariaman; 2). Identifying the effect of several factors of public service ethics at Lubuk Alung Health Center, Padang Pariaman. This research was conducted at the Lubuk Alung Health Center, Padang Pariaman. The sources of this study were the head of health centre, doctors, nurses, midwives, and society. Data collection was done by direct observation, interviews, and documentation. Data analysis was done through the stages of data collection, data reduction, data presentation and conclusion also data validation was done by data triangulation; source, data, and menthod trangulation. The result of this research are; 1). The implementation of public service was done by doctors and nurses in accordance to operational standard. However, there are still few lack of services such as shouted when called the patient queue number and unwelcomed to the old patients who was still confused about terms and services. 2). The employees had followed the dress code policy to be present in professional appearance. 3). Lack of awareness, discipline, patients’s knowledge in treatment procedurs, number of nurses ompare to number of patient, and facility in Lubuk Alung Health Centre, Padang Pariaman become the main factors of lacking pulic service implementation